External Validation of the ELAN‐HF Score, Predicting 6‐Month All‐Cause Mortality in Patients Hospitalized for Acute Decompensated Heart Failure. Issue 14 (16th July 2019) - Salah, Khibar; Stienen, Susan; Moons, Andreas H. M.; Bakx, Adrianus L. M.; van Pol, Petra E.; Kortz, R. A. Mikael; Ferreira, João Pedro; Marques, Irene; Schroeder‐Tanka, Jutta M.; Keijer, Jan T.; Bayes‐Genis, Antoni; Pinto, Yigal M.; et al.
Abstract : Background: Our aim was to calibrate and externally revalidate the ELAN‐HF (European Collaboration on Acute Decompensated Heart Failure) score, to confirm and improve on a previous external validation of the risk score. Methods and Results: The ELAN‐HF score predicts 6‐month all‐cause mortality in patients hospitalized for acute decompensated heart failure using absolute and percentage change of NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) levels in addition to clinical variables. For the external validation, we used the PRIMA II (Can NT‐proBNP–Guided Therapy During Hospital Admission for Acute Decompensated Heart Failure Reduce Mortality and Readmissions?) trial. For both data sets, observed versus predicted mortality was compared for the 4 risk categories; and the mean predicted mortality was plotted against the observed mortality with calculation of a correlation coefficient and SEE. The model discriminant ability was determined by comparing the C‐statistics for both data sets. The predicted versus actual 6‐month mortality values in the derivation cohort were 3.7% versus 3.6% for the low‐risk category, 9.4% versus 9.2% for the intermediate‐risk category, 24.2% versus 23.5% for the high‐risk category, and 54.2% versus 51.1% for the very‐high‐risk category. The correlation between predicted and observed mortality by deciles was 0.92, with an SEE of ±4%. In the validation cohort, predicted versus actual 6‐month mortality values were 3.0% versus 2.2% for the low‐risk category, 9.4% versus 8.2% for the intermediate‐risk category, 25.0% versus 22.9% for the high‐risk category, and 56.8% versus 53.6% for the very‐high‐risk category. The correlation between predicted and actual mortality by quintiles was 0.99, with an SEE of ±2%. There was no significant difference in C‐statistic between the derivation cohort (0.78; 95% CI, 0.74–0.82) and the validation cohort (0.77; 95% CI, 0.69–0.84; P =0.693). Conclusions: Our study confirms that the ELAN‐HF score predicts accurately 6‐month mortality in patients hospitalized for acute decompensated heart failure with the use of easily obtained characteristics.